The Impact of Import Components on Economic Growth in Egypt, Standard Study for the Period (1991-2018) - Qasim, Khalat (Humanities Journal of University of Zakho, 2020)
Foreign trade plays an important and effective role, alongside with exports and imports, in providing growth and economic development requirements, and in achieving high growth rates in Improving individual’s standard living condition, and that the impact of imports is no less important than the impact of exports in achieving it, by providing the necessary goods and services that cannot be produced locally Due to its high costs, on the other hand, by providing goods, intermediate and investment services to move the economic growth forward and achieve economic stability. The research aims to identify the imports and a standard analysis of the impact of the components of imports on the process of economic growth in Egypt for the period 1991-2018, and for that the standard descriptive and analytical method was adopted using the ARDL method to measure the stability of the time series and to indicate the balance relationship between imports and economic growth in the short and long terms, and among the most important results of the research, there is a long-term joint integration relationship between economic growth and import components included within the standard model, in addition to the significant impact of each of the total economic capital compositions and the imports of agricultural commodities on economic growth and with low rates so that doesn’t satisfy the needs of the national economy.